Can Open Science Advance Health Justice? Genomic Research Dissemination in the Evolving Data-Sharing Landscape - Kraft, Stephanie A. (The Hastings Center report, 2024)
Scientific data-sharing and open science initiatives are increasingly important mechanisms for advancing the impact of genomic research. These mechanisms are being implemented as growing attention is paid to the need to improve the inclusion of research participants from marginalized and underrepresented groups. Together, these efforts aim to promote equitable advancements in genomic medicine. However, if not guided by community-informed protections, these efforts may harm the very participants and communities they aim to benefit. This essay examines potential benefits and harms of open science and explores how to advance a more just vision of open science in genomics. Drawing on relational ethics frameworks, we argue that researchers should consider their obligations to participants as well as the broader communities that are impacted by their research. We propose eight strategies to provide a foundation of practical steps for researchers to reduce the possibility of harms stemming from open science and to work toward genomic justice.